Resposta da pressão arterial pulmonar ao esforço físico em pacientes com Estenose mitral - Sanny Cristina de Castro Faria (2016)
Introduction: The clinical presentation of rheumatic mitral stenosis (MS) varies widely and symptoms may be inconsistent with the standard measurements of MS severity. Pulmonary hypertension is a main determinant of functional capacity and cannot be determined by the stenotic lesion itself. Additionally, the factors related to an inappropriately increased pulmonary pressure at exercise are not well defined. Objective: This study assessed the parameters associated with pulmonary pressure response to exercise in patients with isolated MS. Methods: Eighty-four MS patients, 95% females, aged 44.9 ± 10.4 years, 17 in atrial fibrillation, underwent exercise echocardiography with bicycle. Conventional echocardiography was performed a range of echocardiographic parameters were obtained at baseline and at exercise peak. Net atrioventricular compliance (Cn) was estimated at baseline using the equation: Cn (ml/mmHg) = 1270 × (mitral valve area [cm2]/E-wave downslope [cm/s2]). Exercise test were continued until target heart rate was reached or significant symptoms developed. Results: Exercise was stopped for dyspnea (67.9%) or fatigue (21.4%), duration of 482.8 ± 174.0 sec and peak workload of 68.9 ± 22.5 Watts. The systolic pulmonary artery pressure (SPAP) increased from 37.6 ± 13.8mmHg at rest to 64.9 ± 19.7 mmHg during exercise (p < 0.001). Similarly, the transmitral gradients increased significantly from at rest to peak exercise (p < 0.001). Several echocardiographic parameters at rest were associated with SPAP at exercise peak, including mean transvalvular gradient, mitral valve area (MVA), left atrial (LA) diameter, right ventricular function and Cn. By multivariate analysis, mean transvalvular gradient, LA diameter, MVA and Cn were independently associated with SPAP at exercise peak, after adjusting for peak exercise heart rate. Conclusion: In MS patients, baseline mean transvalvular gradient, LA diameter, MVA, and Cn were important determinants of exercise-induced pulmonary hypertension.